Exploring the potential of biscuits as snacks to promote the consumption of biofortified beans - Abu Linus Akawus; Feumba Dibanda Romelle; Nyhalah Dinga Jerome; Panyoo Akdowa Emmanuel; Mbieji Kemayou Christelle Flavie; Mboukap Ntongme Alix; Bernard Tiencheu; Achidi Aduni Ufuan (Discover Food)
Abstract Nutritional deficiencies affect millions of people worldwide and contribute to increased physical, cognitive and immune dysfunction among vulnerable groups. Biofortified beans are being grown to enhance nutrient intake, and snacking can considerably contribute to the promotion of biofortified beans. This study investigated the suitability of biofortified beans in the production of biscuits. Biscuits were formulated by substituting wheat flour with malted fortified bean flour at levels of 0, 25, 50, 75, and 100%. Total iron and zinc content, proximate composition, antinutrient content as well as physical and sensory properties of formulated biscuits were evaluated. Iron, fibers, protein, energy and ash contents increased while zinc and lipid contents decreased with the incorporation of malted fortified bean flour. Analysis of antinutrients showed no significant difference between oxalate and phytate content irrespective of the biscuit formula. The spread ratio, tenderness, and lightness of all bean-based biscuits decreased significantly with increasing proportions of malted bean flour. Biscuits containing 25% of malted fortified bean flour were the most preferred among the beans-based biscuits due to their sensory attributes close to the biscuit control. This study demonstrated the suitability of biofortified beans in the formulation of nutrients-rich biscuits.